Protective effect of ethanolic extract of white oyster mushroom on morphological rat sperm damage due to cigarette smoke exposure - Santun Bhekti Rahimah; Rio Dananjaya; Ermina Widyastuti; Yudi Feriandi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: Cigarettes smokes are a great external source of free radicals. The negative effects of cigarette smoke exposure can be systemic and affect all body systems, including the reproductive. Male rats exposed to cigarette smoke have a risk of oxidative stress and sperm damage. This can be overcome with herbal antioxidants such as white oyster mushrooms (Pleurotus ostreatus).Objective: This study aimed to examine the protective effect of ethanolic extract of white oyster mushroom against damage to sperm morphology of rats exposed to cigarette smoke.Methods: This study is an experimental study using 40 rats which were divided into 5 groups. Group I (normal control), group II (negative control) were only given exposure of cigarette smoke, Grups III, IV and V (treatments groups 1, 2, and 3) were given exposure of cigarette smoke and ethanolic extract a dose of 125, 250, and 500 mg/Kg BW/day for 14 days. On the 15th day, the percentage normal rat sperm were calculated under a 400x magnification microscope.Results: Normal sperm count in group I was 79% ± 0.79, group II was 39% ± 0.55, Grup III, IV and V were 56% ± 0.15, 65% ± 0.54 and 66% ± 0.21.